Volunteer Farmer Trainer program reaching 352,000 dairy farmers in Uganda increases knowledge and productivity - CGIAR Research Program on Policies, Institutions, and Markets (2020)
Since 2012, PIM has supported efforts by ICRAF and partners to implement the volunteer farmer trainer approach in Eastern Africa. As of 2018, 86 organizations across Eastern Africa have adopted the volunteer farmer trainer approach. These organizations work with 17,600 volunteer farmer trainers and serve 352,000 farmers. An impact evaluation found that the use of this approach improved farmers’ knowledge of dairy practices as well as dairy productivity and revenues in Uganda’s Busoga region.